Mangrove Ecosystem Restoration - Sharma, Sahadev (IntechOpen, 2021)
Mangroves serve as one of the nature-based solutions for coastal communities. We are now almost at the tipping point where we can restore mangroves ecologically to mitigate climate change and enhance other important ecosystem services under the United Nations Decade on Ecosystem Restoration. Mangrove Ecosystem Restoration focuses on mangrove ecosystem restoration, the ecosystem services mangroves provide, and how to manage and conserve mangroves. The three sections include eight chapters that cover such topics as evaluating mangrove degradation, forest recovery through seedling recruitment, natural regeneration of mangroves, advanced molecular biology for restoring mangroves, and more.